Chemical composition and antimicrobial activity of the essential oil of Desmostachya bipinnata linn. - K. Ashok Kumar; Sharvanee; Jitendra Patel; Ram Kumar Choudhary (International Journal of Phytomedicine, 2010)
The present study describes the phytochemical profile and antibacterial activity of Desmostachya bipinnata. The sample of essential oil was obtained from the aerial parts of the plant by hydrodistillation and analyzed by GC–MS. From the 16 compounds representing 99.97% of the oils: camphene (16.79%), isobornyl acetate (9.92%), tricyclene (4.30%), (+,-) trans-2,6-gamma-Irone (2.21%), Caryophyllene diepoxide (12.29%) , β-eudesmol (11.16%) Eseroline (25.15%) and Calarene (3.48%) appear as the main components. The oil also contained smaller percentages of Diphenyliodinium bromide, 1.limenone, 2-cyclohexene-1-one and 8-nitro-12-tridecanolide. Furthermore, an antibacterial study of the oil was evaluated using agar diffusion and broth dilution methods. The antibacterial studies showed that the oil had significant inhibitory effect against all four bacteria strains included in the study. Results, suggest potential antibacterial activity of the essential oil of Desmostachya bipinnata, which may find its application in future research for the therapy, food and pharmaceutical industry.